Diplomacy of Indonesia's Natuna National Geopark toward a UNESCO Global Geopark - Hutabarat, Leonard Felix (Masyarakat, Kebudayaan dan Politik, 2023)
This article explains the current overview of the UNESCO Global Geoparks condition in Indonesia as well as putting public diplomacy of Indonesian UNESCO Global Geoparks into a global context. This article will be useful for all stakeholders involved in developing Indonesian UNESCO Global Geoparks in the future. An analysis of the challenges and lessons learned from Natuna is combined in this study with the views of individual stakeholders in Indonesia. Contextual information about the importance of Indonesian tourism of UNESCO Global Geoparks is derived from many references as well as documents. The research adopts a qualitative method. The analysis explains the circumstances of lack of enthusiasm at this time toward the UNESCO Global Geoparks concept by respective stakeholders in Indonesia. There is a need to see UNESCO Global Geoparks as part of efforts to achieve some of the Sustainable Development Goals for 2030. The Indonesian government accepts the idea of UNESCO Global Geopark growth, which can become an approach in post-COVID-19 tourism recovery planning as well as part of the SDGs' 2030 goals in Indonesia. Future development of Indonesian UNESCO Global Geoparks in the global context is important for Indonesian public diplomacy and very significant for the COVID-19 recovery of the Indonesian leisure industry and in line with the UNESCO Sustainable Development Goals 2030.